A study on Islamic loans compared to conventional loans / Saiful Amir Shahidan - Shahidan, Saiful Amir (1994)
This analytical study done on trends of Islamic loans compared to Conventional loans from 1984 to 1993. Least square method is applied to identify the factors determining the trends indicated. The purpose of this study is to know which loan is more profitable. Furthermore, other analysis being made on both loans according to their efficiency in processing loans and computing the loan repayment.